Screening for fetal spina bifida at the 11–13‐week scan using three anatomical features of the posterior brain. (23rd September 2013) - Mangione, R.; Dhombres, F.; Lelong, N.; Amat, S.; Atoub, F.; Friszer, S.; Khoshnood, B.; Jouannic, J.‐M.
ABSTRACT Objective To evaluate the contribution of examination of specific anatomical features of the fetal posterior brain on mid‐sagittal first‐trimester ultrasound examination to the early detection of open spina bifida. Methods Four independent observers reviewed a series of 260 mid‐sagittal first‐trimester ultrasound images from 52 cases of open spina bifida and 208 normal fetuses. The following analysis was performed by each reviewer for each image: Herman score calculation, intracranial translucency score (CFEF‐IT) calculation and determination of presence or absence of three anatomical criteria: intracranial translucency (IT), caudal displacement of the brainstem and cisterna magna. The sensitivity and the false‐positive rate for spina bifida detection were calculated for each of the latter three criteria. A secondary analysis was performed on the subset of images achieving a Herman score ≥ 7. Results The highest detection rate for spina bifida was achieved by non‐visualization of the cisterna magna, with associated sensitivity of 50–73% and 39–76%, respectively, for all images and for the subset of images achieving a Herman score ≥ 7. Posterior shift of the brainstem achieved the highest detection rate (86%), but for a single reviewer only. The level of variation in performance between observers was also greatest for this sign. Absence of IT was associated with a lower detection rate for all observers. Overall, an abnormal posterior brain presenting at least one of these three criteria was associated with a detection rate ranging from 50 to 90%. Conclusion In the detection of spina bifida, non‐visualization of the cisterna magna achieved the best screening performance. Both non‐visualization of the IT and posterior shift of the brainstem were associated with acceptable but lower detection rates. A prospective evaluation of changes in the posterior brain is needed to allow assessment of the most pertinent criteria for first‐trimester screening for spina bifida. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.